Protocol for generating high-fidelity proteomic profiles using DROPPS - Matthew Waas; Meinusha Govindarajan; Amanda Khoo; Charlotte Zuo; Aastha Aastha; Jilin He; Michael Woolman; Annie Ha; Brian Lin; Thomas Kislinger (STAR Protocols)
Summary: Deep mass spectrometry-based proteomic profiling of rare cell populations has been constrained by sample input requirements. Here, we present a protocol for droplet-based one-pot preparation for proteomic samples (DROPPS), an accessible low-input platform that generates high-fidelity proteomic profiles of 100–2,500 cells. We describe steps for depositing cellular material, cell lysis, and digesting proteins in the same microliter-droplet well. We anticipate DROPPS will accelerate biology-driven proteomic research for a multitude of rare cell populations.For complete details on the use and execution of this protocol, please refer to Waas et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.